The condensed protocols from Molecular cloning A Laboratory manual - Sambrook, Joseph (Cold Spring Harbor Laboratory Press, 2006)
This text contains the step-by-step portions of the protocols from 'Molecular Cloning'. Each protocol in this work is cross-referenced to the appropriate pages in the original book, directing the reader to the relevant sections to ensure that they understand the full context of their experiments.